EFFECT OF DIFFERENT SHADE LEVELS ON GENERATIVE GROWTH of Asystasia gangetica (L.) subsp. Micrantha ON THE THIRD CUTTING - K., Nurdiansah; Witariadi, N.M.; Kusumawati, N.N.C. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
Research to determine the effect of various levels of shade on the generative growth of Asystasia gangetica (L.) subsp. Micrantha on the third cutting. The experiment was carried out in Sading Village, Mengwi District, Badung Regency, and lasted for eight weeks, using a completely randomized design (CRD) consisting of four treatments and seven replications with a total of 28 experimental units. The shade level treatment for plants N0: shade 0%; N1: shade 20%; N2: shade 40%; and N3: shade 60%. The variables to observed were the number of inflorescences, number of flowers, number of pods, number of seeds, time to first flowering and weight of seeds. The results showed that the level of shade significantly influenced the growth number of inflorescences, number of flowers, number of pods, time to first flowering, number of seeds and seed weight. It can be concluded that a shade level of 60% (N3) provides the slowest generative growth of Asystasia gangetica plants and is the best treatment.